Sistem Penampil Stok Kendaraan pada Carpool di Perusahaan Otomotif - Melvin Nurohman; Kiki Prawiroredjo; Engelin Shintadewi Julian (Jetri : Jurnal Ilmiah Teknik Elektro, 2020)
The prototype of vehicle stock information display system in PT Krama Yudha Tiga Berlian Motor's carpool is based on the problem of delivering real-time vehicle stock information and inefficient processing of vehicle stock data. The function of this system is to convey information of the number of vehicle stock, the remaining parking slots and vehicles in and out in realtime. This prototype has Android applications, desktop applications, website applications and automatic portals. Based on the results of testing the Android application, the average scan time for barcode scanning of vehicles in and out carpool is 2,47 seconds and for the application of barcode scanning of vehicles locations in carpool is 2,36 seconds. The average transition time between web pages is 20,16 seconds. The average response time for gate in portal is 1,36 seconds and gate out portal is 3,36 seconds.                                                                                              Prototipe sistem penampil stok kendaraan di carpool PT Krama Yudha Tiga Berlian Motor didasari dari masalah penyampaian informasi stok kendaraan yang tidak real time dan tidak efisiennya mengolah data stok kendaraan. Prototipe sistem ini bertujuan untuk menyampaikan informasi jumlah stok kendaraan, sisa slot parkir, kendaraan masuk dan keluar secara real time. Prototipe ini memiliki aplikasi Android, aplikasi desktop, aplikasi website dan portal otomatis. Berdasarkan hasil pengujian scan barcode kendaraan pada aplikasi Android, rata-rata waktu scan 2,47 detik untuk aplikasi scan barcode kendaraan masuk dan keluar dan 2,36 detik untuk aplikasi scan barcode letak kendaraan di carpool. Waktu rata-rata transisi antar halaman website adalah 20,16 detik. Waktu rata-rata respon portal gate in adalah 1,36 detik dan gate out 3,36 detik.